Capillary Lactate Level in Non-Severe and Severe CommunityAcquired Pneumonia Patients - Resti Yudhawati; Kowiy Akbar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Community-acquired pneumonia is an inflammatory disease of the lung caused bymicroorganisms acquired from a non-hospital environment. The pneumonia severity index and ATS/IDSAseverity criteria are widely used to predict the severity of CAP. Lactate is a biomarker that can be measuredby point-of-care devices that provide results in a short of time. This study aimed to determine the differencein capillary lactate level between non-severe and severe pneumonia to provide an additional method toquickly stratify pneumonia severity and treat it accordingly.Methods: This cross-sectional study was performed in the emergency room of a regional research hospital.The pneumonia diagnosis was determined by the symptoms, physical examination and radiological findings.Capillary lactate level was measured with Accutrend Plus lactate point-of care device. Severity stratificationwas done according to ATS/IDSA criteria. The mean of lactate level in all subjects was 3.40±1.52, in nonsevere pneumonia subgroup was 2.25±0.94, and 4.56±1.01 in severe pneumonia subgroup. Lactate issignificantly higher in severe pneumonia subgroup. The cut-off point of lactate level for severity group was3.2 mmol/L (95.5% sensitivity, 86.4% specificity).Conclusion: The early prediction of CAP severity is essential to determine the need for admission in theintensive care unit and close follow up. The lactate level can be used for immediate severity stratification inemergency departments.